2018
DOI: 10.1186/s13054-018-2049-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiles in community-acquired pneumonia: developing assessment tools for disease severity

Abstract: BackgroundThis study aimed to determine whether community-acquired pneumonia (CAP) had a metabolic profile and whether this profile can be used for disease severity assessment.MethodsA total of 175 individuals including 119 CAP patients and 56 controls were enrolled and divided into two cohorts. Serum samples from a discovery cohort (n = 102, including 38 non-severe CAP, 30 severe CAP, and 34 age and sex-matched controls) were determined by untargeted ultra-high-performance liquid chromatography with tandem ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 36 publications
(33 reference statements)
2
42
0
Order By: Relevance
“…Sphingolipids are an important part of the structure of biological membranes and has complex biological functions, such as mediating inflammation [28], regulating proliferation, signal transduction, and migration of cells, as well as apoptosis [29][30]. Previous studies have shown significant changes in sphingolipid metabolism pathways in BALF [9] and serum [31] in CAP patients. Imbalances in the sphingolipid metabolism pathways also occur in other lung inflammatory diseases, such as asthma [32] and chronic obstructive pulmonary disease [33].…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids are an important part of the structure of biological membranes and has complex biological functions, such as mediating inflammation [28], regulating proliferation, signal transduction, and migration of cells, as well as apoptosis [29][30]. Previous studies have shown significant changes in sphingolipid metabolism pathways in BALF [9] and serum [31] in CAP patients. Imbalances in the sphingolipid metabolism pathways also occur in other lung inflammatory diseases, such as asthma [32] and chronic obstructive pulmonary disease [33].…”
Section: Discussionmentioning
confidence: 99%
“…A separate group used 1D 1H nuclear magnetic resonance (NMR) spectra to generate metabolic profiles from 15 patients with pneumonia; comparing the metabolic profiles using Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) they were able to differentiate cases of VAP from those without [104]. Finally, Ning et al analyzed 119 patients with CAP and found markedly different metabolic patterns as assessed by liquid chromatographymass spectrometry (LC-MS) compared with control patients [105]. Sphinganine, p-Cresol sulfate, and DHEA-S were significantly lower, and in combination with lactate, this panel could dis-criminate severe CAP from non-severe CAP with an impressive AUC of 0.911, better than the CURB-65, PSI, and APACHE II scores [105].…”
Section: Metabolomics and Lipidomicsmentioning
confidence: 99%
“…Finally, Ning et al analyzed 119 patients with CAP and found markedly different metabolic patterns as assessed by liquid chromatographymass spectrometry (LC-MS) compared with control patients [105]. Sphinganine, p-Cresol sulfate, and DHEA-S were significantly lower, and in combination with lactate, this panel could dis-criminate severe CAP from non-severe CAP with an impressive AUC of 0.911, better than the CURB-65, PSI, and APACHE II scores [105].…”
Section: Metabolomics and Lipidomicsmentioning
confidence: 99%
“…nutrition and drug treatment) and internal microbiome influences. Metabolites are dynamic analytes present in biological fluids, including urine, producing unique signatures that are readily detected with mass spectrometry and are currently being studied in patients with pneumonia [17][18][19][20] . While these studies have made great strides in elucidating underlying mechanisms of pneumonia and determined some promising biomarkers for specific causative agents, none have combined metabolomics and microbial-omics nor expanded from the discovery phase to algorithmic predictive modeling.…”
Section: Introductionmentioning
confidence: 99%